Knowledge Regarding Ebola Virus Disease among Nursing Students - Adhikari, Mina; Shrestha, Susmita; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2023)
Background: Ebola virus disease (EVD) is an acute, viral and fatal illness among humans and other primates. It can be transmitted from wild animals to human and could spread from human to human. The objective of the study was to assess the knowledge regarding Ebola Virus Disease among the nursing students. Method: A cross sectional analytical study design was conducted among the nursing students to assess the knowledge regarding Ebola Virus Disease among the nursing students of Bharatpur, Chitwan. A total of 138 nursing students were selected by using the enumerative sampling method. Data were collected by using semi structured self-administered questionnaire. Data was entered and analyzed by using SPSS-20. Result: In the study, out of 138 respondents, majority of respondents were in age group of 21-25 years (51.4%) and while least 0.7% were in age group of 26-30years. Regarding ethnicity, highest percentage of the respondents were Brahmin/Chhetri covering 67.4%. Regarding the level of knowledge on Ebola virus disease, 77.5% had poor knowledge and 22.5% had good knowledge. There was statistically significant relationship between the level of knowledge regarding Ebola virus disease and types of family (p<0.031). Conclusion: Based on the finding of the study, it is concluded that majority of the respondents had poor level of knowledge regarding Ebola Virus disease. So, the study recommends the need of effective awareness programme for the nursing students that could bring more awareness as a whole in good level.